Study of The Standards of Job Performance Evaluation Applied on Lattakia and Tartous Ports - Tayoub, Mahmoud; Omran, Tarek (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف هذا البحث إلى التعرف على معايير تقويم الأداء الوظيفي في مرفأي اللاذقية وطرطوس، من خلال التطرق إلى مفهوم معايير التقويم وأهميتها، والمراحل التي يجب أن تمر بها عملية وضع المعايير. وذلك من أجل الوصول إلى الغاية المرجوة من عملية التقويم وهي تحسين الأداء وتطويره. وكان من أهم النتائج التي توصل إليها هذا البحث ما يلي: 1- إن معايير تقويم الأداء المطبّقة في مرفأي اللاذقية وطرطوس لا تعبر بشكل دقيق عن مستوى الأداء المطلوب، حيث تعطي تقديرات متقاربة للجميع. إضافةً إلى ذلك فهي تتعامل مع جميع الأعمال المرفئية بنفس الأهمية. 2- توجد فروق جوهرية بين معايير تقويم الأداء الوظيفي المطبّقة في المرفأين ، ومعايير التقويم الموضوعية المبنية على أسس علمية مدروسة، وهذه الفروق ليست في صالح مجتمع البحث. This research aims at identifying the standards of job performance evaluation used in Lattakia and Tartous ports, by explaining the concept and the importance of the evaluation standards, and phases of evaluation standards in order to get the desired results of the evaluation, i.e.: develop performance. The study concluded the following results:1-The performance evaluation standards used in Lattakia and Tartous ports don’t determine accurately the level of performance, that they apply the same evaluation for all port functions. As well as the standards assign the same importance for all ports jobs 2- There are significant statistical differences between the standards used in both ports and the objective evaluation standards which depend on scientific rules and this difference aren't in advantages of this study.